Pelatihan K3 dan Kebalawistaan sebagai Penunjang Wisata Tirta bagi Siswa SMK Sawan - Nana Trianasari; Ni Luh Henny Andayani; Fridayana Yudiaatmaja (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2022)
Knowledge of Occupational Health and Safety (K3) possessed by workers is one of the critical elements in the smooth operation of an organization or company. Especially for those who are related to hazardous work or related to things that have the potential to cause accidents. Activities related to nature, such as the sea, also require certain skills to minimize accidents. Mastery of K3 and Balawistaan in particular needs to be possessed by SMK students who will switch to the world of work. Therefore, it is necessary to provide introduction, debriefing, and training about this to SMK students as a generation that will soon be involved in the industrial.